"A GAS CHROMATOGRAPHIC METHOD FOR THE DETERMINATION OF INDIVIDUAL FREE FATTY ACIDS IN SERUM" - H. Mohammadiha (Tehran University of Medical Sciences, 1977)
Serum fatty acids on 30 healthy lranian women were detemined by a gas chromatographic method. Oleic and stearic acids were used as standards. The mean values were myristic acid 5. 7% , palmitic acid 43% , palmitoleic acid 5.3% , stearic acid 8% , oleic acid 21. 3% and linleic acid 16.4% of total fatty acid serum contents.